Fostering EFL/ESL Students' State Motivation: The Role of Teacher-Student Rapport - Meng, Yanzhi (Frontiers in Psychology, 2021)
It is maintained that one of the significant determining issues of success is motivation, and enhancing EFL/ESL students’ motivation is dominant in cultivating their learning in the classroom. Moreover, teachers are reflected as the most noteworthy figure of any scholastic organization and the positive rapport between student-teachers is significant for learners’ state motivation. In line with the investigations of teacher-student rapport, principles from positive psychology (PP), and motivational theories such as self-determination and rhetorical/relational goal theory, the present theoretical review seeks this type of relationship and its effects on learners’ motivation. Student-teacher rapport results in progressive practices for learners, as well as superior classroom involvement and motivation. Subsequently, the helpfulness of findings for teachers, learners, materials developers, and teacher trainers are conferred.